Aksi dan Identitas Kolektif Gerakan Islam Radikal di Indonesia - Eric Hiariej (Jurnal Ilmu Sosial dan Ilmu Politik, 2010)
Since 2000 the world has witnessed the rise of Islamic radicalism in Southeast Asia. This paper would like to see Islamic radicalism as a social movement by focusing on the process of collective identity formation. The author argues that collective action is not a given reality but is the outcome of the construction and consolidation of internal identity. That is why without understanding the construction of internal coherence; it is difficult to understand the logic of actions undertaken by the activists. This paper draws analysis from five radical islam organizations: Forum Komunikasi Ahlus Sunnah wal Jamaah (FKASWJ) and its military wing Laskar Jihad (LJ), Front Pembela Islam (FPI), Majelis Mujahidin Indonesia (MMI), Hizbut Tahrir Indonesia (HTI) and Jamaah Islamiyah (JI).